Pendugaan Cadangan Karbon Above Ground Biomass pada Taman Kota Ahmad Yani di Kota Medan - Novita Ariani Sitorus; Rahmawaty Rahmawaty; Abdul Rauf (Program studi Kehutanan USU, 2014)
Global warming is the main enviromental problems of this millennium. Carbon dioxide (CO2) is the main cause for global warming. Green open space such as urban park play a role in mitigating global warming in urban area because the vegetation that is capable to absorb CO2 from the atmosphere through photosynthesis. This study aimed to calculate the carbon stock in all types of vegetation in Urban Park Ahmad Yani. The research was conducted since January until May 2013. The research was conducted at Ahmad Yani Urban Park. The introduction of plants species and measurements had taken by census method and the method of carbon stock data counting was using non destructive sampling, namely the allometric model. The results showed that the value of carbon stock in Urban Park Ahmad Yani is 61,48555 ton/ha.Key words: urban park Ahmad Yani, carbon stock, above ground biomass